Does political connection moderate women directors’ effect on CSR disclosure? Evidence from Malaysia - Intan Maiza Abd Rahman,; Nurul Nazlia Jamil,; Ku Nor Izah Ku Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The objectives of this paper are: to examine the moderating effect of government ownership on the relationship between women directors and corporate social responsibility (CSR) disclosure; and to study the moderating effect of politicians on boards on the relationship between women directors and corporate social responsibility (CSR) disclosure. This paper gathered information from companies’ annual reports for the year 2013. From a sample of 300 non-financial companies listed on Bursa Malaysia, this paper found that government ownership positively moderates women directors’ effect on CSR disclosure, while politicians on boards negatively moderate the effect. Results of this study add to the literature on factors influencing women directors in their process of making decisions from the view of a developing country. As different variables of political connections affect CSR disclosure differently, companies may decide the most suitable situations to adapt to ensure the companies can perform at its best. The findings may further alert policy makers to establish special provision of the appointment on board of directors with political interest.